Chemical Quality of Native Chicken Meat Given a Rationer Containing Fermented Japanese Papaya Leaf Flour (Cindoscolus Aconitifolius) - I Gusti Ayu Dewi Seri Rejeki; Ni Made Yudiastari; Ni Ketut Etty Suwitary; Ni Ketut Sri Rukmini (Formosa Journal of Multidisciplinary Research, 2024)
The need for animal protein originating from native chickens is increasing over time. One of the obstacles that farmers often face in raising broiler chickens is the cost of feed. That feed costs are 60-70% of total production costs. Japanese papaya leaves are one of the substitute feeds that can be given to native chickens. However, Japanese papaya leaves must be fermented first. The nutritional content of Japanese papaya leaves in 100 grams, namely: water 85 ml, protein 5.7 grams, iron 11.4 mg, phosphorus 39 mg, calcium 199 mg, potassium 217 mg, vitamin C 165 mg, flavonoids (23.72 %) alkaloids (17.45%), saponins (12.49%) and tannins (5.72%). This research was carried out in two stages, namely in the field and the laboratory, using a completely randomised design with five treatments and three replications, each containing five chickens. The five treatments are Ration, adding 0%,6%,12%,18% and 24% fermented papaya leaf flour. After harvest, chemical analysis of native chicken meat will be conducted at the Basic Laboratory of the Faculty of Agriculture, Warmadewa University. Adding fermented Japanese papaya leaf flour to native chicken feed does not affect the meat quality of native chickens. However, it tends to increase the protein content of the meat even though statistically, it has no significant effect. Using the fermentation method, utilising agricultural waste can improve the quality of feed ingredients.